2014
DOI: 10.1039/c4md00135d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cyclohexapeptides as antimalarial and anti-trypanosomal agents

Abstract: Azolic and non-azolic cyclohexapeptides were obtained and/or evaluated as promising antimalarial and/or anti-trypanosomal agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…In 2014, Peña et al reported the synthesis and antimalarial and antitrypanosomal activity of seven novel cyclohexapeptides 15 – 21 with 20 and 21 incorporating interesting thiazole functionality [ 37 ]. The study was prompted by earlier reports of cyanobacterium Microcystis aeruginosa PCC 7806 natural products, aerucyclamides A–D ( Figure 4 ), which displayed promising micromolar IC 50 (50% of maximal inhibitory concentration) values against a K1 chloroquine-resistant strain of Plasmodium falciparum [ 38 , 39 ].…”
Section: Solid-phase Synthesis Of Cyclohexapeptides Using Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2014, Peña et al reported the synthesis and antimalarial and antitrypanosomal activity of seven novel cyclohexapeptides 15 – 21 with 20 and 21 incorporating interesting thiazole functionality [ 37 ]. The study was prompted by earlier reports of cyanobacterium Microcystis aeruginosa PCC 7806 natural products, aerucyclamides A–D ( Figure 4 ), which displayed promising micromolar IC 50 (50% of maximal inhibitory concentration) values against a K1 chloroquine-resistant strain of Plasmodium falciparum [ 38 , 39 ].…”
Section: Solid-phase Synthesis Of Cyclohexapeptides Using Solutionmentioning
confidence: 99%
“…After cleavage of linear hexapeptides from the resin using 1% TFA in DCM, macrocyclizations were performed using HBTU, DIPEA, and catalytic 4-dimethylaminopyridine (DMAP) in DCM under dilute conditions (1–5 mM). The coupling site for macrocyclization was chosen to occur at N -terminal glycine for 15 , C -terminal glycine for 17 – 19 , or C -terminal thiazole for 20 – 21 , as this provided the least degree of steric hindrance, resulting in favorable yields [ 37 ]. Moreover, cyclization of linear precursors to afford 17 – 21 took place at a C -terminal glycine or thiazole to prevent epimerization.…”
Section: Solid-phase Synthesis Of Cyclohexapeptides Using Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) [35], as promising antimalarials with EC 50 values in the low micromolar or submicromolar range, respectively [36]. Considering these results, we decided to explore the "old" and versatile drug Ntz, its metabolite Tiz and bis-heterocycles analogs as part of a research program for the synthesis of potential antimalarials [37][38][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…As part of a research program for the synthesis of potential antimalarials [37][38][39][40][41][42][43][44][45][46][47], in this work, we present the synthesis and biological evaluation against P. falciparum 3 D7 of Ntz, Tiz and 2-aminothiazole analogues, Figure 2. Compounds of A series do not present the nitro substituent in the thiazole ring in order to study the in uence of that group in the antimalarial activity.…”
Section: Introductionmentioning
confidence: 99%